(untitled) (Raparin Journal of Humanities (RJH), 2024)
A Conflict as a technique of novel has a vital role in the of configuring the events and characters in the novel and the novelist often bases the plot of his novel on conflict. The conflict itself depends on the nature of relationship between the characters, as well as the conflict and contradiction between the characters or other components of the novel, which eventually creates a rational state, or contradiction between them. This study, from the perspective of the structure of the novel, attempts to explain the conflict of the characters and its types, while at the same time identifying the reasons behind the events and the reasons that cause the characters to fall into conflict. The novel “The Sad Bird’s Nest” is one of the novels that is generally based on the idea of conflict and starts with the conflict of characters at the beginning of the narrative and then extends to the depth of events and the conflicts between the characters themselves, or characters and society. From this perspective, in this study we have tried to identify the types of conflicts, the causes of conflicts and their role in promoting events At first, we have explained the concept of conflict, and relationship between conflict and literature, in another topic we have discussed the personality conflict in the novel, In the last topic, we showed the kinds of conflicts in this novel. Finally, we have shown research result with some points and references that we used in the research. The results of the research shown that conflict affects the behavior of the characters and causes changes in the thinking and understanding of the characters in the novel "The Sad Bird’s Nest", so that each of the characters, "Kamrani Salma, Khalid Amun, Mansour Asrin" attitude towards about love and their life.